2014
DOI: 10.1007/s00216-014-8246-1
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-functionalized porous phospholipid nanoshells for direct measurement of Hg2+ in urine

Abstract: A porous phospholipid nanoshell (PPN) sensor functionalized with a specific aptamer sensor agent was prepared for rapid detection of Hg2+ in human urine with minimal sample preparation. Aptamer sensors provide an important class of optical transducers that can be readily and reproducibly synthesized. A key limitation of aptamer sensors, and many other optical sensors, is the potential of biofouling or biodegradation when used in complex biological matrices such as serum or urine, particularly when high levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…This indicated that the complex sample matrices originating from biological samples significantly disturbed the recognition capability of the FAB toward Hg 2+ . In addition, it was reported that the low compatibility of FABs toward biological samples was mainly due to the degradation of FABs by the DNase in complex matrices. ,, To verify that the challenges with biological samples originated from the sample matrices, the recognition of Hg 2+ by FAB in water samples with and without DNase were compared as shown in Figure C. The experimental results confirmed the previous observations and verified the hypothesis in Figure B that the complex sample matrices in biological samples significantly disturbed the recognition capability of FABs.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This indicated that the complex sample matrices originating from biological samples significantly disturbed the recognition capability of the FAB toward Hg 2+ . In addition, it was reported that the low compatibility of FABs toward biological samples was mainly due to the degradation of FABs by the DNase in complex matrices. ,, To verify that the challenges with biological samples originated from the sample matrices, the recognition of Hg 2+ by FAB in water samples with and without DNase were compared as shown in Figure C. The experimental results confirmed the previous observations and verified the hypothesis in Figure B that the complex sample matrices in biological samples significantly disturbed the recognition capability of FABs.…”
Section: Resultssupporting
confidence: 81%
“…As reported, although the modified aptamers were resistant to nuclease digestion, these modifications might affect the aptamer structure and its function (recognition capability). 11 Alternatively, the integration of aptamer beacons with nanomaterials such as porous phospholipid nanoshells, 15 polyacrylamide nanoparticles, 16 DNA hydrogels, 17 carbon nanotubes, 18 T h i s c o n t e n t i s graphene oxides, 19 and gold nanoparticles 20 was another efficient way to increase the biocompatibility of FABs, since the nanomaterials could impede the interaction between the aptamer beacons and the interference substances. However, the aptamer modification and nanomaterial integration might increase the difficulty in the synthesis of FABs.…”
mentioning
confidence: 99%
“…As explained previously, the fluorescent emission of the dyes can also be attenuated by a quencher linked to the opposite termini of the sensitive aptamer. One which has been widely employed with this aim is 4-([4-(dimethylamino)phenyl]azo)benzoic acid (DABCYL) [66], owing to its broad absorption spectrum [67]: the sensor reported by Li and co-authors [68] presented a linear calibration curve between 10 nM and 200 nM, with a LOD of 10 nM Hg 2+ . Furthermore, in order to avoid the biodegradation of the aptamer, it was encapsulated in a porous phospholipid nanoshell (PPN), allowing its utilization in human urine samples.…”
Section: Heavy Metal Ion Sensors Based On Fluorescent Aptamersmentioning
confidence: 99%
“…The utilization of this sequence involves a key advantage over other ON sequence-based Hg 2+ sensors, as the T-Hg 2+ -T mismatches absorb the electrons emitted by the labelled atto390 (consequently quenching the fluorescent emission), there is no need to use either a quencher [31] or a complementary sequence [32]. This also allows the sequence to become directly attached onto the optical fiber, as it is explained hereafter.…”
Section: Chemicals and Reagents For The Fabrication Of The Sensormentioning
confidence: 99%